Simplicidad divina radical - Alvarado, José Tomás (TheoLogica, 2024)
Many philosophers have combined a Platonic metaphysics about abstract entities and a theistic conception according to which God is the creator of ‘heaven and earth’, of all ‘visible and ‘invisible’. Supposedly, God is the unique entity a se, i. e., the unique entity on which every other depends ontologically. It has been a traditional contention of Platonists, nevertheless, that abstract things, like universals or numbers, are independent. How are these theses compatible? Several critics have argued that they are not. A theist ontology imposes —for them— the outright rejection of Platonism or, eventually, a milder form of Platonism that substitutes universals and other abstracta by ‘concepts’ or ‘ideas’ in the divine intellect. Philosophers of Platonic convictions have tried to assuage the conflict introducing restrictions in divine aseity or by subjecting universals to some form of ‘absolute creation’. None of these attempts has been successful. In this work a different approach is presented and defended. It is argued that the universal of ‘deity’, W, is identical to God. This is a radicalization of the doctrine of divine simplicity.